Identification of phenolamine in rape bee pollen and its protective effect and mechanism on alcoholic liver injury - Cheng Lü; Mingjuan Xu; Xinbiao Yang; Yanlun Feng; Yun Zhu; Qun Lu; Chengming Wang; Rui Liu (Food Science and Human Wellness)
Rape bee pollen has attracted increasing interests for its excellent protective effect against chemical-induced liver injury owing to its abundant polyphenols. This study aims to analyze the types and contents of phenolamides (seldom concerned) in rape bee pollen and their protective mechanism on alcoholic liver disease (ALD). Different from the previous finding that flavonoids are dominant polyphenols in bee pollen polyphenolic extract, our results demonstrated that there are only three flavonoids but 24 phenolamides in the as-prepared rape bee pollen phenolic extract (PPE). In addition, PPE was found to significantly improve the viability (from 54.9% to 84.1%, 89.2%, and 94.0%) of alcohol-induced AML12 cells and alleviate alcohol-induced cell apoptosis (from 28.5% to 22.89%, 22.0%, and 17.4%). To dissect the underlying mechanism for the protective effect of PPE against ALD, the molecular pathway was identified by RNA-seq analysis. Transcriptome data revealed that PPE may protect against ALD by decreasing inflammation, cholesterol, and fatty acid synthesis (P < 0.05). The National Institute on Alcohol Abuse and Alcoholism (NIAAA) model was used to further evaluate the hepatoprotective effect of PPE in vivo, and the results validated that PPE could alleviate liver injury and hepatic steatosis (from 22.7% to 11.5% and 10.9%) induced by alcohol. As the dominant polyphenols in PPE, phenolamides can be a class of valuable polyphenolic compounds in bee pollen with the potential to alleviate ALD.